A Letter to Ahmad Khan - I.M. Mirgaleev; I.R. Gibadullin (Золотоордынское обозрение, 2016)
We bring to attention of specialists an undated letter of Ottoman ruler Mehmed II Fatih to the Great Horde khan Ahmad from the collection of famous collector of Ottoman charters Feridun-bey [1, S. 289]. The addressee is the famous ruler of the Great Horde, khan Ahmad. Daulat Khan mentioned in the letter is Nur-Davlet. He was connected with khan Ahmad, and, as indicated by the letter, he had also set in close contact with the Ottomans whose ruler openly declares in a letter that “our sight of benevolence and patronage is directed toward him”. Thereby the Sultan made it clear to the “principal” Tatar khan Akhmad that Nur-Davlet was under the patronage of the Ottoman Empire. Considering the period of activity of Nur-Davlet in Crimea, presumably the letter was written in 1477. Famous researcher of the Crimean Khanate V.D. Smirnov had already examined the letter and the question of why Ahmad Khan was named the Crimean khan in the title of the letter [2, p. 221–222].